Pengaruh Faktor Eksternal Terhadap Harga Saham: Analisis Dengan Data Historis Dari Yahoo Finance - Zebua, Melianus; Gea, Elviani (CV. SINAR HOWUHOWU, 2025)
This research investigates the impact of external factors on stock prices by analyzing historical data from Yahoo Finance. The study aims to comprehensively examine how global events, international news, and macroeconomic indicators influence stock market dynamics. Utilizing a mixed-method approach combining quantitative time series analysis and qualitative event study methodology, we analyzed stock price movements across multiple sectors during significant global events between 2018-2023. The research employed advanced statistical techniques including multiple regression, event study methodology, and correlation analysis to identify and quantify the relationship between external factors and stock price variations. Results demonstrated that geopolitical events, economic policy changes, and international health crises significantly influence stock price volatility, with correlation coefficients ranging from 0.65 to 0.85 across different market sectors. The study provides crucial insights for investors, policymakers, and financial analysts in understanding the complex interplay between external factors and stock market performance.